Male gamete biology in flowering plants. (22nd March 2010) - Russell, Scott D.; Gou, Xiaoping; Wei, Xiaoping; Yuan, Tong
Abstract : Flowering plant reproduction is characterized by double fertilization, in which two diminutive brother sperm cells initiate embryo and endosperm. The role of the male gamete, although studied structurally for over a century at various levels, is still being explored on a molecular and cellular level. The potential of the male to influence development has been historically underestimated and the reasons for this are obvious: limitations provided by maternal imprinting, the much greater cellular volume of female gametes and the general paucity of paternal effects. However, as more is known about molecular expression of chromatin-modifying proteins, ubiquitin pathway proteins and transcription factors in sperm cells, as well as their ability to achieve effect by intaglio expression, passing transcripts directly into translation, the role of the male is likely to expand. Much of the expression in the male germline that appears to be distinct from patterns of pollen vegetative cell expression may be the result of chromosomal level regulation of transcription.